The Gospel code : novel claims about Jesus, Mary Magdalene, and Da Vinci - Witherington, Ben, III, 1951- (Downers Grove, Ill. : InterVarsity Press, 2004)
In plain language that any interested reader can follow, the author, a New Testament scholar, responds to fictionalized claims in The Da Vinci Code that there exist documents that reveal secrets about Jesus, secrets long suppressed by the church and other religious institutions. He takes us back to the early centuries after Jesus' death and tells us what we can really know about Jesus, Mary Magdalene, the canonical Gospels and their Gnostic rivals
A novel idea? -- No weddings and a funeral -- Tell me the old, old story -- His story, history and the canon's story -- Mary Magdalene and the new gnosticism -- Something about Mary -- Those in the know -- Doubting Thomas -- Did the canon misfire? -- Consulting the canon professors -- Reading Borg again for the first time -- What if God was one of us? -- Postscript: truth decay in the twenty-first century
Includes bibliographical references (pages 201-202) and indexes
Keywords: Brown, Dan, -- 1964-; Mary Magdalene, -- Saint -- In literature; Jesus Christ -- In literature; Christian saints in literature; Christianity in literature